Improving joint performance of friction stir welded 2195-O Al–Li alloy by post-weld heat treatment and rolling deformation - Jiaxin Chen; Rong Chen; Hongfei Liao; Yuanyuan He; Peng Chen; Ye Tian; Bo Zhang; Zhiqing Zhang (Journal of Materials Research and Technology, 2024)
Post-weld heat treatment and rolling deformation are used to improve the mechanical properties of 2195-O Al–Li alloy friction stir welding (FSW) joints, and the effects on the grain structure, precipitation behaviors, hardness distribution, and tensile performance are discussed. Microstructural characterization was conducted using scanning electron microscopy (SEM), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM). Mechanical properties were measured by hardness test and tensile test. Results show that coarse precipitates are subjected to various degrees of dissolution after FSW. Solution treatment following artificial aging (SAA) and 40% rolling deformation + SAA treatment (R40-SAA) enables the dissolution of coarse precipitates completely and precipitation of strengthening phases (T1 and θ′) in the nugget zone (NZ), thermo-mechanically affected zone and heat-affected zone (HAZ). These strengthening precipitates have little difference in precipitation behavior after SAA and R40-SAA treatment and remain consistent across all regions, resulting in joint hardness change a little between these two joints with a homogeneous distribution. The change in precipitates leads to an increase in hardness and enhances both the SAA joint strength and the R40-SAA joint strength to 503 MPa and 528 MPa (superior to the original joints by 309 MPa and 334 MPa, respectively), respectively. The SAA joints fracture in the NZ resulting from the development of AGG, and develop an intergranular fracture morphology with an elongation of 4.2%. The R40-SAA joints have an elongation of 7.2% due to the generation of uniformly fine grains in the NZ, and fail in the HAZ exhibiting a brittle fracture mechanism.